2023
DOI: 10.3390/met13020299
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Design of Fatigue-Testing Fixture for Artificial Cervical Disc Prostheses

Abstract: To investigate the biomechanical performances of artificial cervical disc (ACD) prostheses, many studies have been conducted, either with cervical sections of cadavers under physiological loads or with block-like testing fixtures obeying the ASTM F2346 standard. Unfortunately, both methods are almost impossible to utilize for accurate results of lifetime anti-fatigue experiments for at least 10 million cycles due to the difficulties in cadaver preservation and great deviations of natural cervical bodies, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…It is well known that the mechanical properties of medical implants have a significant impact on the in vivo performances after implantation, and biomimetic simulation and finite element analysis are effective methods for investigating the mechanical properties and in vivo stability of implants. Considering the structural features of natural human cervical, Cheng et al [2] designed a new fixture for measuring the fatigue properties of artificial cervical disc (ACD) prostheses under different mechanical conditions, including flexion, extension, and lateral bending. The numerical simulations and mechanical experiments were carried out to characterize the equivalence between the designed fixture and the natural cervical sections, and the results indicated that this novel biomimetic fixture could reflect the biomechanical characters of the natural human cervical vertebrae with acceptable accuracy.…”
Section: Contributionsmentioning
confidence: 99%
“…It is well known that the mechanical properties of medical implants have a significant impact on the in vivo performances after implantation, and biomimetic simulation and finite element analysis are effective methods for investigating the mechanical properties and in vivo stability of implants. Considering the structural features of natural human cervical, Cheng et al [2] designed a new fixture for measuring the fatigue properties of artificial cervical disc (ACD) prostheses under different mechanical conditions, including flexion, extension, and lateral bending. The numerical simulations and mechanical experiments were carried out to characterize the equivalence between the designed fixture and the natural cervical sections, and the results indicated that this novel biomimetic fixture could reflect the biomechanical characters of the natural human cervical vertebrae with acceptable accuracy.…”
Section: Contributionsmentioning
confidence: 99%